Preparation method of metal ceramic cutter suitable for titanium alloy blade disc machining and metal ceramic cutter
Through powder metallurgy technology and high-frequency alternating electric field sintering technology, metal cermet tools with high saturation free carbon were prepared, solving the problems of low processing efficiency and serious wear of titanium alloy blades, and achieving high strength, high hardness and high thermal conductivity The tool improves processing efficiency and surface quality.
Patent Information
- Application Number
- CN202411101114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-12
AI Technical Summary
During the processing of titanium alloy blade disks, metal cermet tools have low processing efficiency and severe wear due to material characteristics. The thin-wall bonds and high chemical reactivity of the blade structure cause cutting force and heat to intensify vibration, affecting surface integrity and roughness .
Powder metallurgy technology is used to prepare high-saturated free carbon metallurgy tools, and quickly sintered in a high-frequency alternating electric field to form a gradient temperature field and carbon atom distribution, improving the hardness and thermal conductivity of the tool.
It improves the processing efficiency of titanium alloy blade disks, reduces or eliminates processing wear, enhances the high strength, high hardness and high thermal conductivity of the tool, and improves the integrity and roughness of the blade disk surface.
Smart Images

Figure CN119216581A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal ceramics, and in particular relates to a preparation method of a metal ceramic tool suitable for machining titanium alloy blade disks and the metal ceramic tool. Background Art
[0002] Metal ceramics are widely used in the field of aviation cutting tools due to their good hardness, excellent wear resistance and corrosion resistance. However, when processing the integral blade disk, since the main component of the blade disk is titanium alloy, the material has the characteristics of low thermal conductivity, high strength and high chemical reactivity. During the machining process, the high cutting temperature in the micro-area often causes the tool adhesion wear and diffusion wear to increase, which leads to low tool processing efficiency. In addition, since the overall blade structure is mostly thin-walled keys, the rigidity at the blade tip is poor. Excessive cutting force and cutting heat can easily increase the finishing vibration, which in turn has an adverse effect on the surface integrity, roughness and thickness tolerance of the blade. Summary of the invention
[0003] In order to solve the problems of low processing efficiency and severe processing wear of metal ceramic tool blades, the present invention provides a method for preparing a metal ceramic tool suitable for processing titanium alloy blades. The metal ceramic tool prepared by this method has the characteristics of high strength and high hardness, can improve the processing efficiency of the blade, and reduce or eliminate processing wear.
[0004] The invention also provides a metal ceramic tool suitable for machining titanium alloy blade disks.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk, the preparation method comprising:
[0007] S1. Preparation of metal ceramic tool specimens with high saturated free carbon by powder metallurgy process;
[0008] S2. In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300°C at a rate of 100-120°C / s, and then rapidly cooled to 500±20°C in an inert atmosphere;
[0009] S3. After cooling in step S2, the metal ceramic tool sample is rapidly heated to 1000-1300°C under vacuum conditions, and then rapidly cooled to 500°C±20°C under an inert atmosphere;
[0010] S4. Repeat step S3 several times, and finally cool to room temperature to obtain a metal ceramic tool suitable for titanium alloy blade disk processing.
[0011] Furthermore, the method of preparing a metal ceramic tool sample having high saturated free carbon by using a powder metallurgy process specifically includes:
[0012] MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere to obtain metal ceramic tool samples with high saturated free carbon.
[0013] Wherein, the MeC powder includes at least one of TiC, WC and TaC;
[0014] Alternatively, the MeC powder is a solid solution powder formed by at least two of TiC, WC and TaC;
[0015] In the green body, the mass ratio of MeC powder, Ni powder and nickel-coated activated carbon powder is 85:10:5.
[0016] Furthermore, the mixing of MeC powder, Ni powder and nickel-coated activated carbon powder is pressed into a green body, and sintered in an inert atmosphere to obtain a metal ceramic tool sample with high saturated free carbon, specifically comprising:
[0017] MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere at a sintering pressure of 5±0.5MPa and a sintering temperature of 1450±20℃. The mixture was kept at 1450℃ for 1h to obtain a metal ceramic tool sample with high saturated free carbon.
[0018] Wherein, the particle sizes of the MeC powder, the Ni powder and the nickel-coated activated carbon powder are 1.2um, 1.5um and 1um respectively.
[0019] Furthermore, the size of the green body is 20×6.5×5.25 mm.
[0020] Furthermore, the nickel-coated activated carbon powder is prepared by the following method:
[0021] The activated carbon powder is evenly dispersed in the SnCl2 solution, and then the temperature is raised to 50-70°C and kept warm for a certain period of time to obtain solution A;
[0022] Adding PaCl2 to the solution A to perform surface activation treatment on the activated carbon powder to obtain solution B;
[0023] Adding NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate to the solution B to obtain a solution C;
[0024] The pH of the solution C is adjusted to 10-13.2, and then reacted at 40-60° C. for 1-3 hours until the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm, thereby obtaining a solution D;
[0025] The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder.
[0026] Furthermore, the nickel-coated activated carbon powder is prepared by the following method:
[0027] Activated carbon powder with a particle size of 50nm-200nm is uniformly dispersed in a 2-20g / L SnCl2 solution, and then the temperature is raised to 50-70°C and kept warm for 1-1.5h, and ultrasonic oscillation is used during the warming period to obtain solution A;
[0028] Adding PaCl2 to the solution A to perform surface activation treatment on the activated carbon powder for 60-90 min to obtain solution B;
[0029] Adding NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate (Na2CO3N2H4.H2O) to the solution B to obtain a solution C;
[0030] The pH of the solution C is adjusted to 10-13.2, and then reacted at 40-60° C. for 1-3 hours until the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm, thereby obtaining a solution D;
[0031] The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder;
[0032] Wherein, the concentration of activated carbon powder in the solution A is 1 to 2.5 g / L;
[0033] The concentration of PaCl2 in the solution B is 0.1-0.3 g / L;
[0034] The concentrations of NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate in the solution C are 0.1-0.3 g / L, 0.5-1 g / L and 0.8-1.4 g / L respectively.
[0035] Furthermore, in a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300° C. at a rate of 100-120° C. / s, and then rapidly cooled to 500±20° C. in an inert atmosphere, specifically comprising:
[0036] In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300° C. at a rate of 100-120° C. / s, and then cooled to 500° C.±20° C. within 5-8 seconds in an inert atmosphere;
[0037] The vacuum degree of the vacuum environment is 2×10 -3 -6×10 -3 Pa;
[0038] The frequency of the high-frequency alternating electric field is 50-85 MHZ, the current is 2-8A, and the voltage is 380-500V.
[0039] Furthermore, after the cooling in step S2 is completed, the metal ceramic tool sample is rapidly heated to 1000-1300° C. under vacuum conditions, and then rapidly cooled to 500° C.±20° C. under an inert atmosphere, specifically comprising:
[0040] After cooling in step S2, the metal ceramic tool sample is heated to 1000-1300°C within 5-8s under vacuum conditions, and then cooled to 500°C±20°C within 5-8s under an inert atmosphere.
[0041] Furthermore, in step S4, step S3 is repeated 10-50 times.
[0042] Based on the same inventive concept, the present invention provides a metal ceramic tool suitable for machining titanium alloy blade disks. The metal ceramic tool is prepared by the above-mentioned method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks.
[0043] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0044] 1. The present invention discloses a method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks. The method adopts a powder metallurgy process to sinter a metal ceramic sample with high saturated free carbon, and then utilizes a high-frequency alternating electric field to assist rapid sintering to generate a temperature field with a gradient. Along the direction of the temperature field, the concentration of free carbon atoms in the sample will produce a gradient distribution. Due to the conjugation effect of carbon atoms and nickel atoms, the surface layer of the tool will present a high carbide distribution and the sub-surface layer will present a high metal phase distribution, so that the surface of the tool presents high hardness and high wear resistance, and the heat generated by cutting is quickly discharged along with the sub-surface metal, thereby preparing a metal ceramic tool with high strength, high hardness and high thermal conductivity, which can improve the machining efficiency of the blade disk and reduce or eliminate machining wear.
[0045] 2. The present invention discloses a method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks. The method utilizes a high-frequency alternating electric field to assist sintering to produce a high-speed dynamically changing temperature field, that is, during rapid heating and rapid cooling, the surface temperature of the metal ceramic sample is higher than the internal temperature, forming a temperature field extending from the surface downward to the internal area. Under the action of the temperature field, carbon atoms with small mass and small radius are prone to diffusion, and more vacancies exist in the surface crystals with high temperature, and the crystals have larger lattice parameters. During the whole process, carbon atoms tend to migrate from the sub-surface area to the surface area. Therefore, a composition gradient corresponding to the temperature field gradient is generated, that is, the carbon atom concentration distribution is gradiently distributed along the direction of the temperature field, thereby preparing a metal ceramic with a hard surface and tough core and a gradient distribution of carbon atoms.
[0046] 3. The present invention provides a method for preparing a metal ceramic tool suitable for titanium alloy blade disk processing. Before the powder metallurgy process is carried out, activated carbon powder is wrapped with nickel, which can reduce the mutual diffusion between C atoms and carbides MeC before the nickel liquidus appears, and reduce the solid dissolution of C atoms by carbide crystal cells during sintering. After the liquidus appears, most of the C atoms can be dissolved in nickel, and nickel as a carrier has better fluidity, which is conducive to the formation of a gradient distribution of C atoms under the action of the temperature field. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0048] Figure 1 This is the EDS element distribution diagram of the metal ceramic tool that was cyclically treated 30 times in a high-speed changing dynamic temperature field.
[0049] Figure 2 This is the cutting force change diagram of the metal ceramic tool after 30 times of temperature field treatment and the ordinary metal ceramic tool cutting titanium alloy under the same parameters.
[0050] Figure 3 This is the hardness distribution of the gradient metal ceramic after temperature field treatment. DETAILED DESCRIPTION
[0051] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0052] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0053] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0054] The technical principle of the present invention is as follows:
[0055] A method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk, the method comprising:
[0056] S1. Preparation of metal ceramic tool specimens with high saturated free carbon by powder metallurgy process;
[0057] S2. In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300°C at a rate of 100-120°C / s, and then rapidly cooled to 500±20°C in an inert atmosphere;
[0058] S3. After cooling in step S2, the metal ceramic tool sample is rapidly heated to 1000-1300°C under vacuum conditions, and then rapidly cooled to 500°C±20°C under an inert atmosphere;
[0059] S4. Repeat step S3 several times, and finally cool to room temperature to obtain a metal ceramic tool suitable for titanium alloy blade disk processing.
[0060] Step S1 specifically includes:
[0061] MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere to obtain metal ceramic tool samples with high saturated free carbon.
[0062] Wherein, the MeC powder includes at least one of TiC, WC and TaC;
[0063] Alternatively, the MeC powder is a solid solution powder formed by at least two of TiC, WC and TaC;
[0064] In the green body, the mass ratio of MeC powder, Ni powder and nickel-coated activated carbon powder is 85:10:5.
[0065] In the present invention, the advantage of using at least one of TiC, WC and TaC in MeC powder is that the three types of powders have good high temperature creep resistance, and the hardness of the material itself is high, and the produced tool is more wear-resistant. In the green body, the mass ratio of MeC powder, Ni powder and nickel-coated activated carbon powder is 85:10:5, which has the advantage that the tool matrix has good fracture toughness, reduces brittleness and prevents tool chipping, and uses Ni as a bonding phase, which has better wettability and solid solution strengthening makes the bonding phase more wear-resistant.
[0066] More specifically, step S1 includes:
[0067] MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere at a sintering pressure of 5±0.5MPa and a sintering temperature of 1450±20℃. The mixture was kept at 1450℃ for 1h to obtain a metal ceramic tool sample with high saturated free carbon.
[0068] Wherein, the particle sizes of the MeC powder, the Ni powder and the nickel-coated activated carbon powder are 1.2um, 1.5um and 1um respectively.
[0069] The size of the green body is 20×6.5×5.25 mm.
[0070] In the present invention, the advantage of the green body sintering temperature of 1450±20℃ is that the sintering temperature is the main dissolution temperature of Ni, but not the dissolution temperature of MEC powder. In this condition, the metal is easy to undergo solid solution, which can effectively enhance the basic mechanical properties of the liquid phase. At the same time, the hard phase can refine the grains through dissolution-precipitation, making the grain size of the matrix smaller. If the temperature is too low, the grain dissolution process is slow, and the free energy obtained by the metal particles is low, resulting in incomplete solid solution reaction. It is more likely that the Ni bonding phase will evaporate during the sintering process, reducing the bonding phase of the matrix and reducing the strength of the matrix. The advantages of using the above-mentioned particle size range for the MeC powder, the Ni powder and the nickel-coated activated carbon powder are that the powder has good fluidity, and the matrix hard phase and liquid phase manufactured with a powder particle size of about 1um are uniform and not easy to produce segregation. The size of the green body is 20×6.5×5.25mm, which is a common tool material detection size. When made into this size, transverse rupture strength, coating, hardness, density, magnetic force and magnetic saturation can be detected.
[0071] In step S1, the nickel-coated activated carbon powder is prepared by the following method:
[0072] The activated carbon powder is evenly dispersed in the SnCl2 solution, and then the temperature is raised to 50-70°C and kept warm for a certain period of time to obtain solution A;
[0073] Adding PaCl2 to the solution A to perform surface activation treatment on the activated carbon powder to obtain solution B;
[0074] Adding NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate to the solution B to obtain a solution C;
[0075] The pH of the solution C is adjusted to 10-13.2, and then reacted at 40-60° C. for 1-3 hours until the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm, thereby obtaining a solution D;
[0076] The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder.
[0077] In the present invention, the activated carbon powder is uniformly dispersed in the SnCl2 solution, and then the temperature is raised to 50-70°C in order to increase the kinetic energy of the liquid to facilitate a full reaction. The advantage of using PaCl2 to perform surface activation treatment on the activated carbon powder is that the solution only performs surface activation treatment on the object, does not participate in other reactions and is easy to remove. The purpose of adding sodium citrate and anhydrous sodium carbonate hydrazine hydrate to the solution B is to promote the coating of the powder.
[0078] In the present invention, the pH of the solution C is adjusted to 10-13.2 for the purpose of neutralizing the influence of the acidic reagent. The advantage of the Ni layer thickness growing on the surface of the activated carbon powder exceeding 0.5 μm is that the Ni powder particle size is protected to maintain its original shape during the ball milling process. If it is too thick, the C content will increase, and if it is too thin, it may not be able to protect the Ni powder well.
[0079] Step S2 specifically includes:
[0080] In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300° C. at a rate of 100-120° C. / s, and then cooled to 500° C.±20° C. within 5-8 seconds in an inert atmosphere;
[0081] The vacuum degree of the vacuum environment is 2×10 -3 -6×10 -3 Pa;
[0082] The frequency of the high-frequency alternating electric field is 50-85 MHZ, the current is 2-8A, and the voltage is 380-500V.
[0083] In the present invention, the purpose of placing the metal ceramic tool sample in a high-frequency alternating electric field for rapid heating and rapid cooling is that the sudden change in the electric field environment can effectively eliminate the defects generated during the crystallization process of the matrix. The high-frequency alternating electric field has a frequency of 50-85MHZ, has a good treatment effect, and requires a short reaction time.
[0084] Step S3 specifically includes:
[0085] After cooling in step S2, the metal ceramic tool sample is heated to 1000-1300°C within 5-8s under vacuum conditions, and then cooled to 500°C±20°C within 5-8s under an inert atmosphere.
[0086] In the present invention, the purpose of heating the metal ceramic tool sample to 1000-1300°C within 5 to 8 seconds is to remove impurities (binders) inside the metal sample and activate the powder particle size. If the heating rate and target temperature are too high, the bonding phase will be liquefied, while if they are too low, the powder cannot be fully activated. The purpose of cooling the metal ceramic tool sample to 500°C±20°C within 5 to 8 seconds is to eliminate the defects generated during the pressing process while maintaining partial activity of the powder. If the target cooling temperature is too high, the particles will shrink imperfectly, while if it is too low, the particles will lose their activity.
[0087] In the present invention, the heating process is carried out under vacuum conditions, and the cooling process is carried out under an inert atmosphere. The advantages are that the vacuum prevents the particles from oxidizing, and the pressure is less than the atmospheric pressure, which will make them denser. The inert gas is introduced during cooling to protect and reduce the temperature.
[0088] In step S4, step S3 is repeated 10-50 times.
[0089] In the present invention, the purpose of repeatedly rapidly heating and rapidly cooling the metal ceramic tool sample is to eliminate the residual stress inside the blank. The repetition number of 10-50 times is conducive to obtaining a fine and dense metal ceramic matrix.
[0090] The following will describe in detail a method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk and a metal ceramic tool of the present application in combination with examples and experimental data.
[0091] Example 1
[0092] The present embodiment provides a method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk, which specifically includes:
[0093] (1) Weigh 50 nm activated carbon powder and add it to a 10 g / L SnCl2 aqueous solution to obtain solution A (the final concentration of activated carbon powder is 1.8 g / L). Disperse solution A evenly and heat it to 70 °C for 1 h. Use ultrasonic oscillation to ensure the dispersibility of the powder.
[0094] (2) PaCl2 is added to the solution A, and the concentration of PaCl2 is ensured to be 0.1 g / L, to obtain solution B, so as to perform surface activity treatment on the dispersed activated carbon powder, the treatment time is 60 min, after the treatment is completed, NiSO4 (final concentration 0.2 g / L), sodium citrate (final concentration 0.5 g / L) and anhydrous sodium carbonate hydrazine hydrate (final concentration 1 g / L) are added to solution B to obtain solution C, which contains an effective Na ion concentration of 50 g / L, and NaOH solution is added to solution C to obtain solution D, the pH needs to be maintained at 10, and the powder surface is treated to grow a Ni layer. At this time, the temperature needs to be maintained at 40°C, the treatment time is 1 hour, and the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm.
[0095] (3) The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder.
[0096] (4) Preparation of metal ceramic mixture. The nickel-coated activated carbon powder was fully dried to 5wt.%, and 85wt.% TiC powder and 10wt.% Ni powder were weighed, totaling 300g. This step is to obtain the maximum saturated free C atom content of the Ti-C-Ni three-phase. The powder was milled by a planetary ball mill. The ratio of powder to alloy ball was 0.3:1 during ball milling. Deionized water was used as the ball milling medium. After ball milling for 6 hours, the powder slurry was sieved with a 200-mesh screen. After sieving, it was dried at 70°C. After drying, it was sieved with a 100-mesh screen, and an industrial MW23 molding agent with a powder content of 10% was added to the powder.
[0097] (5) Sintering of metal ceramic tool sample. The mixture prepared in step (4) is pressed into a sample of 20×6.5×5.25 mm under a pressure of 300 MPa, or into a metal ceramic rod blank of the corresponding size of the required end mill. The pressed blank size is D18*120L. The blank is kept at 380°C for 6 hours, the molding agent is removed, and the solid phase is kept near the Ni liquidus line of 1310 degrees Celsius for 3 hours to make the sample initially reach a solid phase dense state. The temperature is then raised to 1450°C and kept for 1 hour. The sintering atmosphere is Ar and the sintering pressure is 5 MPa to obtain a metal ceramic tool sample.
[0098] (6) The metal ceramic tool sample was descaled on the grinding wheel, polished with sandpaper, and cleaned with ethanol ultrasonic wave. Then, it was placed in a high-frequency alternating current vacuum furnace (frequency 50-85 MHZ, current 2-8 A, voltage 380-500 V). The initial temperature was 25 °C, the heating rate was 100 °C / s, and the sample was quickly heated to 1000 °C in about 10 s. The vacuum degree in the furnace was 2 × 10 - 3Pa. Stop heating, cool to 500°C in 5 seconds in Ar gas with a flow rate of 100L / h. Then turn off the argon gas and heat to 1000°C for 5 seconds, turn on the argon gas and cool to 500°C again within 5 seconds. Repeat this step 30 times, and finally cool to room temperature 25°C to obtain a metal ceramic tool.
[0099] After testing, the transverse fracture strength of the metal ceramic tool prepared in this embodiment was measured by a universal fatigue testing machine, and its transverse fracture strength was 2470MPa. The relative density of the matrix was measured by the drainage method and was 99.8%. The surface hardness of the tool was measured by a Vickers hardness tester and was 1810HV. 30 , fracture toughness is 9.7MPam 1 / 2 The friction coefficient when grinding with titanium alloy is 0.15, and the main cutting force when cutting titanium alloy is less than 280N. It has excellent mechanical properties.
[0100] Example 2
[0101] The present embodiment provides a method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk, which specifically includes:
[0102] (1) Weigh activated carbon powder of 200 nm and add it to a 20 g / L SnCl2 aqueous solution to obtain solution A (the final concentration of activated carbon powder is 2.2 g / L). Disperse solution A evenly and heat it to 70°C for 90 min. During this time, ultrasonic oscillation is used to ensure the dispersibility of the powder.
[0103] (2) PaCl2 is added to the solution A, and the concentration of PaCl2 is ensured to be 0.3 g / L, to obtain solution B, so as to perform surface activity treatment on the dispersed activated carbon powder, the treatment time is 60 min, after the treatment is completed, NiSO4 (0.2 g / L), sodium citrate (0.8 g / L) and anhydrous sodium carbonate hydrazine hydrate (1.2 g / L) are added to solution B to obtain solution C, which contains an effective Na ion concentration of 70 g / L, and NaOH solution is added to solution C to obtain solution D, the pH needs to be maintained at 13.2, and a Ni layer is grown on the powder surface. At this time, the temperature needs to be maintained at 60°C, the treatment time is 3 hours, and the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm.
[0104] (3) The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder.
[0105] (4) Preparation of metal ceramic mixture. The nickel-coated activated carbon powder was fully dried to 5wt.%, and 85wt.% WC powder and 10wt.% Ni powder were weighed, totaling 300g. This step was to obtain the maximum saturated free C atom content of the WC-Ni three-phase. The powder was milled by a planetary ball mill. The ratio of powder to alloy ball was 0.3:1 during ball milling. Deionized water was used as the ball milling medium. After ball milling for 4h, the powder slurry was sieved with a 200-mesh screen. After sieving, it was dried at 70°C. After drying, it was sieved with a 100-mesh screen, and an industrial MW23 molding agent with a powder content of 10% was added to the powder.
[0106] (5) Sintering of metal ceramic tool sample. The mixture prepared in step (4) is pressed into a sample of 20×6.5×5.25 mm or a metal ceramic rod blank of the required end milling cutter size under a pressure of 300 MPa. The pressed blank size is the same as that in Example 1. The blank is kept at 380°C for 6 hours, the forming agent is removed, and the solid phase is kept near the Ni liquidus line of 1310 degrees Celsius for 3 hours to make the sample initially reach a solid phase dense state. The temperature is then raised to 1450°C and kept for 1 hour. The sintering atmosphere is Ar and the sintering pressure is 5 MPa to obtain a metal ceramic tool sample.
[0107] (6) The metal ceramic tool sample was descaled on the grinding wheel, polished with sandpaper, and cleaned with ethanol ultrasonic wave. It was then placed in a homemade high-frequency alternating current vacuum furnace with an initial temperature of 25 °C and a heating rate of 100 °C / s. The sample was rapidly heated to 1300 °C in about 13 s. The vacuum degree in the furnace was 2 × 10 -3 Pa. Stop heating, cool to 500°C in 10 seconds in Ar gas with a flow rate of 100L / h. Then turn off the argon gas and heat to 1300°C for 8 seconds, turn on the argon gas and cool to 500°C again within 10 seconds. Repeat this step 50 times, and finally cool to room temperature 25°C to obtain a metal ceramic tool.
[0108] After testing, the transverse fracture strength of the metal ceramic tool prepared in this embodiment is 3280MPa, the relative density is 99.6%, and the surface hardness is 1720HV 30 , fracture toughness 11.2MPam 1 / 2 The friction coefficient when grinding with titanium alloy is 0.24, and the main cutting force when cutting titanium alloy is less than 300N. It has excellent mechanical properties.
[0109] Figure 1 Using SEM at 8000 times the diameter, we can observe the coating of C powder by Ni powder particles. It can be seen that C powder forms a uniform coating layer around Ni powder.
[0110] Figure 2The above figure shows the cutting force during the actual machining process of the titanium alloy blade tool prepared in the manner of Example 1 and tested using a Keister 9527B three-phase dynamometer. The cutting is smooth during the machining process, and the maximum cutting force is 194N.
[0111] Figure 2 The figure below shows the cutting force during the actual machining process of the titanium alloy blade rough machining tool prepared in the manner of Example 2, and tested using a Keister9527B three-phase dynamometer. During the machining process, the cutting force decreases from high to low, and the maximum cutting force is 1426N.
[0112] Figure 3 The surface hardness of the rough machining tool substrate for titanium alloy blades prepared in Example 2 was tested using a scratch tester, and the maximum Vickers hardness of the test was 1820 Hv.
[0113] It should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0114] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0115] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks, characterized in that: The preparation method comprises: S1. Preparation of metal ceramic tool specimens with high saturated free carbon by powder metallurgy process; S2. In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300°C at a rate of 100-120°C / s, and then rapidly cooled to 500±20°C in an inert atmosphere; S3. After cooling in step S2, the metal ceramic tool sample is rapidly heated to 1000-1300°C under vacuum conditions, and then rapidly cooled to 500°C±20°C under an inert atmosphere; S4. Repeat step S3 several times, and finally cool to room temperature to obtain a metal ceramic tool suitable for titanium alloy blade disk processing.
2. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 1, characterized in that: The method of preparing a metal ceramic tool sample having high saturated free carbon by using a powder metallurgy process specifically comprises: MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere to obtain metal ceramic tool samples with high saturated free carbon. Wherein, the MeC powder includes at least one of TiC, WC and TaC; Alternatively, the MeC powder is a solid solution powder formed by at least two of TiC, WC and TaC; In the green body, the mass ratio of MeC powder, Ni powder and nickel-coated activated carbon powder is 85:10:
5.
3. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 2, characterized in that: The method comprises mixing MeC powder, Ni powder and nickel-coated activated carbon powder, pressing the mixture into a green body, and sintering the mixture under an inert atmosphere to obtain a metal ceramic tool sample having high saturated free carbon, which specifically comprises: MeC powder, Ni powder and nickel-coated activated carbon powder were mixed and pressed into green compacts, which were sintered in an inert atmosphere at a sintering pressure of 5±0.5MPa and a sintering temperature of 1450±20℃. The mixture was kept at 1450℃ for 1h to obtain a metal ceramic tool sample with high saturated free carbon. Wherein, the particle sizes of the MeC powder, the Ni powder and the nickel-coated activated carbon powder are 1.2um, 1.5um and 1um respectively.
4. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 2, characterized in that: The size of the green body is 20×6.5×5.25 mm.
5. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 2, characterized in that: The nickel-coated activated carbon powder is prepared by the following method: The activated carbon powder is evenly dispersed in the SnCl2 solution, and then the temperature is raised to 50-70°C and kept warm for a certain period of time to obtain solution A; Adding PaCl2 to the solution A to perform surface activation treatment on the activated carbon powder to obtain solution B; Adding NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate to the solution B to obtain a solution C; The pH of the solution C is adjusted to 10-13.2, and then reacted at 40-60° C. for 1-3 hours until the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm, thereby obtaining a solution D; The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder.
6. The method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks according to claim 5, characterized in that: The nickel-coated activated carbon powder is prepared by the following method: Activated carbon powder with a particle size of 50nm-200nm is uniformly dispersed in a 2-20g / L SnCl2 solution, and then the temperature is raised to 50-70°C and kept warm for 1-1.5h, and ultrasonic oscillation is used during the warming period to obtain solution A; Adding PaCl2 to the solution A to perform surface activation treatment on the activated carbon powder for 60-90 min to obtain solution B; Adding NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate to the solution B to obtain a solution C; The pH of the solution C is adjusted to 10-13.2, and then reacted at 40-60° C. for 1-3 hours until the thickness of the Ni layer grown on the surface of the activated carbon powder exceeds 0.5 μm, thereby obtaining a solution D; The solution D is filtered, washed and dried to obtain nickel-coated activated carbon powder; Wherein, the concentration of activated carbon powder in the solution A is 1 to 2.5 g / L; The concentration of PaCl2 in the solution B is 0.1-0.3 g / L; The concentrations of NiSO4, sodium citrate and anhydrous sodium carbonate hydrazine hydrate in the solution C are 0.1-0.3 g / L, 0.5-1 g / L and 0.8-1.4 g / L respectively.
7. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 1, characterized in that: The method of placing the metal ceramic tool sample in a high frequency alternating electric field under a vacuum environment and heating it to 1000-1300° C. at a rate of 100-120° C. / s, and then rapidly cooling it to 500±20° C. under an inert atmosphere, specifically includes: In a vacuum environment, the metal ceramic tool sample is placed in a high-frequency alternating electric field and heated to 1000-1300° C. at a rate of 100-120° C. / s, and then cooled to 500° C.±20° C. within 5-8 seconds in an inert atmosphere; The vacuum degree of the vacuum environment is 2×10 -3 -6×10 -3 Pa; The frequency of the high-frequency alternating electric field is 50-85 MHZ, the current is 2-8A, and the voltage is 380-500V.
8. The method for preparing a metal ceramic tool suitable for machining a titanium alloy blade disk according to claim 1, characterized in that: After the cooling of step S2 is completed, the metal ceramic tool sample is rapidly heated to 1000-1300° C. under vacuum conditions, and then rapidly cooled to 500° C.±20° C. under an inert atmosphere, specifically comprising: After cooling in step S2, the metal ceramic tool sample is heated to 1000-1300°C within 5-8s under vacuum conditions, and then cooled to 500°C±20°C within 5-8s under an inert atmosphere.
9. The method for preparing a metal ceramic tool suitable for machining titanium alloy blade disks according to claim 1, characterized in that: In step S4, step S3 is repeated 10-50 times.
10. A metal ceramic tool suitable for machining titanium alloy blade disks, characterized in that: The metal ceramic tool is prepared by the preparation method of a metal ceramic tool suitable for titanium alloy blade disk processing according to any one of claims 1 to 9.
Citation Information
Patent Citations
Metal ceramic cutter with gradient structure and preparation method thereof
CN101838766A
Ti(C,N) based metal ceramic nitrogen atmosphere sintering process
CN111195724A
New material alloy cutter and preparation method thereof
CN115555565A
Cermet, method for manufacturing the cermet, and cutting tool
JP2014029001A
Surface-toughened cemented carbide bodies and method of manufacture
US5310605A